國民小學教師正向領導對學生幸福感影響之研究：以學生學術樂觀為中介變項 A Study on the Relationship between Teacher Positive Leadership and Student Well-being in Elementary Schools: Student Academic Optimism as a Mediator - 謝傳崇 Chuan-Chung Hsieh; 謝宜君 Yi-Chun Hsieh (National Changhua University of Education, 2016)
本研究旨在了解國民小學教師正向領導、學生學術樂觀與學生幸福感的現況與三者關係。在研究方法上採用問卷調查法，並使用結構方程模式驗證教師正向領導、學生學術樂觀與學生幸福感的關係。本研究編製國民小學教師正向領導、學生學術樂觀與學生幸福感 之問卷，以國民小學六年級學生為研究對象，共蒐集有效問卷822 份，其中男女比例分別為49.6％與50.4％。研究結果顯示學生知覺教師正向領導、學生學術樂觀與學生幸福感之現況具有高度知覺，三者之間具相關性，且影響關係模式適配度良好。雖然教師正向領導對學生幸福感有顯著直接影響效果，但教師正向領導透過學生學術樂觀之中介作用，能對學生幸福感產生更大的影響性，其影響效果也相對的提高。本研究建議教師採用正向領導帶領班級，影響學生學術樂觀，進而提升學生幸福感。 This study aims to investigate the current status and interrelationship of elementary school teacher positive leadership, student academic optimism and student well-being. Questionnaire survey was used as the primary research method in this study. Structural Equation Modeling was adopted in order to verify the linear relationships between teacher positive leadership, student academic optimism, and student well-being. Questionnaires pertaining to the above three variables were developed by the researchers, and administered to a sample of six-graders from selected elementary schools. There were 822 returned questionnaires with valid responses, completed by 49.6% male and 50.4% female six-graders. The results show that students' perceptions of teacher positive leadership, student academic optimism and student well-being are high, and that there are significant positive correlations among the three variables. While students' perceptions of teacher positive leadership has significant direct effect on student wellbeing, the effect is greatly enhanced in extent and in magnitude when mediated by student academic optimism. This study suggests that to improve student's well-being, especially through increased student academic optimism, teacher positive leadership should be widely practiced.